The Effect of Company Size, Company Growth, Leverage and Profitability on Firm Value (Empirical Study of Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2020-2022) - Hamidah, Ulfia Putri; Sundarta, Imam; Syukur, Dudung Abdul (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2023)
The purpose of this study was to determine the effect of firm size, firm growth, leverage and profitability on firm value in manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange in 2020-2022. The method used in sampling is purposive sampling. Purposive sampling is a technique in determining the sample based on certain criteria that will support the variables used. Based on these criteria, the number of samples obtained was 19 companies so that the total observations in this study were 57 observations. The data used in this study is secondary data obtained from financial reports available on the official website of the Indonesia Stock Exchange. Methods of data collection using the method of documentation. The documentation method is carried out by collecting secondary data through audited company financial reports and published on the official website of the Indonesia Stock Exchange. The data analysis method used is multiple linear regression analysis. Based on the results of linear regression analysis with a significance level of 5%, the results of this study conclude that (1) firm size has no effect on Firm Value, (2) firm Growth has a negative and significant effect on Firm Value, (3) Leverage has a positive effect and significant to Firm Value, (4) Profitability has a positive and significant effect on Firm Value.